Reassessment of Pterolepis parnassiifolia (Melastomataceae, Melastomateae) and a new combination for the genus - Freitas, Juliana G.; Santos, Andrea K.a.; Peraza-Flores, Lizandro N. (Phytotaxa, 2019)
We clarified the identity and nomenclature of Pterolepis parnassiifolia. A new combination, Pterolepis piatensis, is also proposed to recognize at species level the previously described P. parnassiifolia var. piatensis. We included full morphological descriptions, photographs, drawings, and discussions on the taxonomy, distribution and conservation of both species. We also included a table of main morphological characters separating P. parnassiifolia from P. piatensis.